Enhancing extraction of proanthocyanidins from Chinese quince fruit by ball-milling and enzyme hydrolysis: yield, structure, and bioactivities - KONG,Wan-Qing (2022)
Abstract Chinese quince fruits are rich in proanthocyanidins (PAs), which have antioxidant properties. This work describes a method to isolate PAs from Chinese quince fruits by a combination of ball-milling and enzyme hydrolysis pretreatments. The yield, total PA and total phenolic contents, structural characteristics, antioxidant activity, and α-amylase inhibitory activity of different pretreated PA samples were determined and analyzed. Among them, the ball-milling combined with multi-enzyme (cellulase, xylanase, and pectinase) hydrolysis pretreated sample (BEP-4) was the most outstanding. The yield of BEP-4 could be improved up to 7.72%, which was 2.51 times higher than that of the conventional organic solvent extraction method (3.02%). It had the highest total phenols and PAs content of 750.98 ± 6.95 and 948.72 ± 3.50 mg/g extract, respectively. The thermal stability and molecular weight (9610 Da) of BEP-4 were lower than other fractions. BEP-4 contained a high proportion of PC structure (98.35%) and flavan-3-ol content (87.88%). It also had the highest antioxidant capacity with IC50 values of 131.45 ± 0.97, 22.66 ± 0.32, 134.05 ± 0.71, and 182.07 ± 0.28 μg/mL for DPPH, ABTS, hydroxyl radical scavenging capacity, and α-amylase inhibiting capacity, respectively. These investigations provide a new, efficient way to isolate PAs from Chinese quince fruits, and reveal that Chinese quince fruits may be a good source of antioxidants, worthy of further development.